Real-world evaluation of perception, convenience and anticoagulant treatment satisfaction of patients with atrial fibrillation switched from long-term vitamin K antagonist treatment to dabigatran. Issue 2 (12th November 2020) - Choi, Eue-Keun; Lee, Young-Soo; Chern, Alan Koay Choon; Jiampo, Panyapat; Chutinet, Aurauma; Hanafy, Dicky Armein; Trivedi, Prabhav; Zhai, Dongmei; Oh, Yong Seog
Abstract : Background and purpose: Real-world data about treatment convenience and satisfaction in Asian non-valvular atrial fibrillation (NVAF) patients after switching from vitamin K antagonists (VKAs) to non-VKA oral anticoagulants were evaluated. Methods: In this non-interventional study involving 49 sites across five countries in Southeast Asia and South Korea, 379 stable NVAF patients who switched from VKA therapy to dabigatran during routine clinical practice were recruited and followed up for 6 months. Treatment convenience and satisfaction were evaluated using Perception on Anticoagulant Treatment Questionnaire-2 (PACT-Q2). Through post hoc analysis, factors associated with improved treatment convenience scores at visit 2 were described. Results: Treatment convenience and satisfaction significantly improved after switching from VKAs to dabigatran at visit 2 and visit 3 (convenience: p<0.001 each vs baseline; satisfaction: p=0.0174 (visit 2), p=0.0004 (visit 3) compared with baseline). Factors predictive of higher (>80th percentile) response on treatment convenience were female sex, younger age (<75 years), higher baseline stroke risk, higher creatinine clearance and absence of concomitant hypertension, stroke or gastrointestinal diseases. Conclusion: Dabigatran was associated with a significant improvement in treatment convenience and satisfaction after switching from VKAs when used for stroke prevention in NVAF patients from Southeast Asia and South Korea.